Diversity and Trade - Grossman, Gene M; Maggi, Giovanni (American Economic Review, 2000)
We develop a competitive model of trade between countries with similar aggregate factor endowments. The trade pattern reflects differences in the distribution of talent across the labor forces of the two countries. The country with a relatively homogeneous population exports the good produced by a technology with complementarities between tasks. The country with a more diverse workforce exports the good for which individual success is more important. Imperfect observability of talent strengthens the forces of comparative advantage. Finally, we examine the effects of trade on income distribution and the composition of firms in each industry. (JEL F11, D51)